(untitled) (Neo Science Peer Reviewed Journal, 2025)
Methods of Organizing and Conducting Athletics Competitions in Secondary Schools Athletics competitions in secondary schools have a significant impact not only on the development of sports but also on students’ physical education. This abstract discusses the essential principles, methodologies, and practices required for effectively organizing competitions. Athletics, with its various events, provides students the opportunity to increase physical activity, create a healthy competitive environment, and foster team spirit. During the process of holding competitions, students not only test their skills but also strengthen friendships and solidarity. The abstract covers key aspects such as planning competitions, selecting venues, preparing participants, and ensuring safety measures. Additionally, innovative approaches to enhancing student motivation and encouraging their involvement in sports are also explored.